2019
DOI: 10.1017/beq.2019.21
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder Dialogue as Agonistic Deliberation: Exploring the Role of Conflict and Self-Interest in Business-NGO Interaction

Abstract: ABSTRACT:Many companies engage in dialogue with nongovernmental organizations (NGOs) about societal issues. The question is what a regulative ideal for such dialogues should be. In the literature on corporate social responsibility (CSR), the Habermasian notion of communicative action is often presented as a regulative ideal for stakeholder dialogue, implying that actors should aim at consensus and set strategic considerations aside. In this article, we argue that in many cases, communicative action is not a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
82
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(95 citation statements)
references
References 77 publications
1
82
0
Order By: Relevance
“…greenwash) and clawback lost legitimacy (Moog et al, 2015) or through marketing that resembles smoke and mirrors (Prasad and Holzinger, 2013). PCSR and MSIs have been questioned for their insensitivity towards impacts on marginalized stakeholders (Banerjee, 2009;Mäkinen & Kourula, 2012;Whelan, 2012;Moog et al, 2013;Dawkins, 2015;Ehrnström-Fuentes;Maher, 2019;Alamgir & Banerjee, 2019;Brand et al, 2019). According to such critiques, research on the deliberative model of PCSR fails to problematize the notion of power in stakeholder engagement (Dawkins, 2015) and, more generally, in deliberative democracy within MSIs (Banerjee, 2009;Moog et al, 2015;Fougère & Solitander, 2019).…”
Section: Good Parenting To Overcome the Shortcomings Of Msismentioning
confidence: 99%
See 2 more Smart Citations
“…greenwash) and clawback lost legitimacy (Moog et al, 2015) or through marketing that resembles smoke and mirrors (Prasad and Holzinger, 2013). PCSR and MSIs have been questioned for their insensitivity towards impacts on marginalized stakeholders (Banerjee, 2009;Mäkinen & Kourula, 2012;Whelan, 2012;Moog et al, 2013;Dawkins, 2015;Ehrnström-Fuentes;Maher, 2019;Alamgir & Banerjee, 2019;Brand et al, 2019). According to such critiques, research on the deliberative model of PCSR fails to problematize the notion of power in stakeholder engagement (Dawkins, 2015) and, more generally, in deliberative democracy within MSIs (Banerjee, 2009;Moog et al, 2015;Fougère & Solitander, 2019).…”
Section: Good Parenting To Overcome the Shortcomings Of Msismentioning
confidence: 99%
“…It is asserted that deliberative democracy cannot deal with the messy realities of everyday politics because of its idealistic assumptions of rational participating actors (Brand et al, 2019). More critical perspectives on extractives-community dialogue, such as Banerjee (2018), warn that an obsession with reaching 'consensus through deliberation obscures processes of domination and disallows spaces of difference and coexistence' (p. 816), thus implying that deliberative processes can be undemocratic.…”
Section: Good Parenting To Overcome the Shortcomings Of Msismentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the context of responsible innovation and particularly where stakeholders perceive their differences as being irreconcilable, the exclusive orientation towards resolution is questionable. A series of recent studies have taken a closer look at this assumption and have concluded that the orientation towards resolution is a way of reducing pluralism of views and, as such, a way of circumventing the many benefits that can result from a pluralist innovation environment (Ligtvoet et al 2016;Cuppen 2012;Brand et al 2020;Blok 2019;Cuppen et al 2019).…”
Section: The Conciliatory Approachmentioning
confidence: 99%
“…These include interpersonal, inter-organizational, institutional, ideological, and discursive contestations, among others (e.g. Gutierrez-Huerter et al, 2020; Hamann et al, 2020; Whelan et al, 2009), while emphasizing elements such as the micro-level dynamics of relational work (Girschik, Svystunova & Lysova 2020; Glavas, 2016; Gond & Moser, 2021; Noronha, D’Cruz & Banday, 2020;), conflict (Brand, Blok & Verweij, 2020), tensions (Mitra & Buzzanell, 2017; Nyberg & Wright, 2013), unintended consequences (Banerjee & Jackson, 2017) and power (Shamir, 2005). Our objectives are three-fold.…”
Section: Introductionmentioning
confidence: 99%